A Literature Review of The Effect of Employer Branding Towards Intention to Apply - Natanael Natanael; Ratna Komala Putri (International Journal of Economics, Business and Innovation Research, 2024)
This literature review explores the impact of employer branding on the intention to apply among prospective job seekers. By analyzing ten recent studies conducted across various geographical and organizational contexts, the review consistently demonstrates that employer branding has a significant and positive influence on individuals' intentions to apply for jobs. Employer branding, which involves creating a favorable image and reputation for a company, is shown to be a crucial factor in attracting potential employees. The findings highlight the importance for companies to invest in and prioritize employer branding as part of their recruitment strategies. By effectively communicating their values, culture, and reputation, companies can enhance their appeal to potential candidates, thereby increasing their intention to apply and strengthening their talent acquisition efforts. This review provides valuable insights for organizations aiming to optimize their recruitment processes through strategic employer branding